Editorial: Self-enquiry as an intrapersonal means to promoting scholarship of professional development: Our quest for new meaning making - du Toit, P.H. (South African Journal of Higher Education, 2018)
Editorial Pieter H du Toit Guest Editor A special edition of SAJHE such as this with a dedicated Section B is not like liquorice allsorts. This section is an exemplar of the work of a scholarly community of practice enriching one another and showing interconnectedness. It has as focus action research/participatory action research, which includes reflexive practice, self-enquiry and auto-ethnography. Different fields of specialisation add to the claim I make that currently higher education practitioners are taking responsibility for monitoring their educational professional development in a scholarly fashion. And there is evidence of interdisciplinary research and interinstitutional collaboration across higher education institutions. Using action research and related research designs and approaches to the research of practice over many years culminates in the evidence-based reporting in the respective articles. Of note is the fact that the practices reported on are innovative. Innovations are to be observed in terms of what higher education practitioners do in their respective practices regarding of instruction and learning. New ideas of how a student-centred approach can be promoted are evident in the article by Belinda Verster who reports on her experience of using the principles of notions revolving around the flipped classroom as a means to promoting quality learning. And innovations are evident in the way these practitioners promote the scholarship of action research, self-enquiry, etc. among their students – ensuring that students are empowered to become independent scholars of the future. The articles are not ordered in a specific way; this shows that all the research projects reported are the scholarly output of a collective. It is a socio-constructivist ethnographic picture. It is not meant to be ordered in a sequential format. It rather is a mix – in terms of institutional affiliation, subject specialisation foci and research designs employed. It is significant that the notion of looking into the self is evident country-wide. Participatory action research gets the attention it deserves in the article by Ansurie Pillay. An action research design informed her study. This design type, or action research per se, gave direction to other studies. Angeline van Wyngaarden and her co-workers found this approach apt for their study. The scholarship of other research approaches, such as auto-ethnography is evident in the work by Sumari O’Neil and Linda Van Laren. Sumari’s deconstructing auto-ethnography brings a new perspective on our view of meaning making. Using auto-ethnography in the context of postgraduate research supervision in itself is innovative. Reporting on supervision practice is neglected in South Africa. More studies of this nature should inform our meaning making in terms of this responsibility most academics have. Linda van Laren makes us aware of the role auto-ethnography can play in terms of a better understanding of HIV/AIDS contexts. In their article Karen Collett and her co-authors promote the expansion of auto-ethnography as a collaborative endeavour. Some of the articles focus on teacher education with specific reference to teaching practice or school visits as a form of work-integrated learning. According to scholars such as Price (2001), Mertler (2008), Mitchener and Jackson (2012) not many studies of teacher education, specifically mentoring pre-service teachers, made use of action research, self-study, auto-ethnography, reflexive practice, etc. The articles with a focus on teacher education are exemplary of the shift that needs to be made – bringing the self (academics and students alike) – into the scholarly picture. This makes for new meaning making that is essential for broadening our current understanding of teacher education in general. New meaning making stems from the fact that constructivism is an epistemological stance that informs all the studies reported, although not spelled out as such in the different articles. Omar Essau’s contribution indicates how pre-service teacher education could contribute to improving schools. If teaching practice is considered a form of community engagement as is the case with some faculties of education in South Africa, the construct service learning comes to the fore. Teaching practice is not merely an opportunity for pre-service teachers in terms of self-development; it is an opportunity to learn from the school community. And it is an opportunity to give back to this community with a view to contributing to its development. Omar focuses specifically on contributing to making schools a safer and enriched environment. The lens Wilfred Molotja and co-author use is specifically on teaching English as subject. The enactment of the importance of reflecting lies with the student teachers. This is an essential attribute of a teacher and is considered one of the attributes of the 21st Century that is often taken in consideration in the literature on professionalism − n this case the teacher as professional. I consider all the contributions as exemplary of the educational professional development of academic staff – the scholars involved in the studies being reported. Siza Makanya reports on this; so do Karen Collett and her co-workers. Again, not all articles refer to this phenomenon. However, inherently all the articles have educational professional development as focus. If we regard professional development as important we need to act as role-models to our students in this regard. Role-modelling is the focus of the article by Anita Hiralaal. Education in Health Sciences in general and nurse education in particular is an important part of the higher education landscape. Two articles are devoted to specialisation in the field of health sciences: the article by Angeline van Wyngaarden and co-authors and the article by Gisela van Rensburg and co-authors. The latter is my deduction as the affiliation of the authors suggests this, although the study refers to students in general. Each article with its specific focus makes a good read. Collectively the articles span a number of aspects that constitute part of the South African higher education landscape as far as practice is concerned. The reader is invited to become part of the scholarly community of practice that contributed to making this Section B of the publication possible. By reading one becomes an important member of the scholarly community of practice; without a reader audience research is conducted in vain.